An investigation into oxidation-induced fragmentation of soot aggregates by Langevin dynamics simulations. (15th February 2023) - Qian, Weijia; Hui, Xin; Wang, Bosen; Kronenburg, Andreas; Sung, Chih-Jen; Lin, Yuzhen
Abstract: The present work proposes a novel oxidation-induced fragmentation model for soot aggregates which is implemented as a submodel in Langevin dynamics (LD) simulations. The surface growth and particle aggregation are first simulated in the LD framework to generate a large number of aggregates with sufficient geometric diversities resembling realistic soot aggregates. The fragmentation of these aggregates induced by surface oxidation through reaction with molecular oxygen at high temperatures is then modelled. The probability density function (PDF) of a newly proposed fragmentation pattern factor is obtained from the statistical analysis of the fragment sizes. The probability of forming a monomer fragment and a remaining aggregate fragment (monomer fragmentation) is found to be two orders of magnitude higher than that of forming two fragments of similar size (equal-sized fragmentation). The relative importance of various aggregate characteristic parameters affecting the fragmentation pattern, i.e., splitting size ratio, is quantified by a Random Forest regression. It is found that the standard deviation of the overlapping coefficient is the most important parameter, followed by the global average overlapping coefficient, number of primary particles, fractal prefactor, and the fractal dimension. An exponential function is fitted to the PDF of the fragmentation pattern factor. The functional form is independent of the aggregate parameters and the fitted function shows good agreements with the statistics of the fragmentation pattern factor. Graphical abstract: Highlights: Novel oxidation-induced fragmentation model for soot aggregates. Statistics of a newly proposed fragmentation pattern factor. Importance of characteristic parameters affecting the fragmentation pattern. An exponential function is fitted to the fragmentation pattern factor.